Double Barriers for Moisture Degradation: Assembly of Hydrolysable Hydrophobic Molecules for Stable Perovskite Solar Cells with High Open‐Circuit Voltage. (28th May 2020) - Guo, Pengfei; Ye, Qian; Liu, Chen; Cao, Fengren; Yang, Xiaokun; Ye, Linfeng; Zhao, Wenhao; Wang, Hongyue; Li, Liang; Wang, Hongqiang
Abstract: The rapid growth in the device efficiency of perovskite solar cells (PSCs) has raised great demands for tackling their long‐term stability upon external environmental stimuli that restricts the commercialization of PSCs, in which the instability upon exposure to moisture has been one of the major obstacles. Herein, an effective way of building up double barriers for moisture degradation of the perovskite films is demonstrated by modifying them with rationally selected hydrolyzable hydrophobic molecules (1H, 1H, 2H, 2H‐perfluorooctyl trichlorosilane, PFTS). The layer of oligomer derived from the hydrolyzed PFTS at the surface that increases the hydrophobicity of perovskite film could serve as an efficient wall preventing the moisture invasion. The long‐term exposure of the film upon moisture allows for the formation of a secondary wall that employs the hydrolyzation of PFTS at grain boundaries, favoring defects passivation to further improve the humidity stability. Such gradual hydrolyzation is encouragingly helpful for the enhancement of the open‐circuit voltage of the PSCs from the original 1.136 up to 1.205 V. The PSCs constructed with the double barriers demonstrate excellent stability upon moisture and improved thermal and light stabilities, as well as a champion power conversion efficiency up to 21.34%. Abstract : An effective strategy is demostrated to create a double barrier that not only blocks the invasion of the moisture but also takes advantage of the permeated moisture to increase the moisture durability of perovskite films, which results in an n–i–p perovskite solar cell with moisture stability over 115 days in a relative humidity of 70% and a champion efficiency up to 21.34%.